2018
DOI: 10.1088/1361-6579/aae6ed
|View full text |Cite
|
Sign up to set email alerts
|

Image-based classification of bladder state using electrical impedance tomography

Abstract: Objective: In this study, we examine the potential of using machine learning classification to determine the bladder state (‘not full’, ‘full’) with electrical impedance tomography (EIT) images of the pelvic region. Accurate classification of these states would enable urinary incontinence (UI) monitoring to alert the patient, before involuntary voiding occurs, in a low-cost and discrete manner. Approach: Using both numerical and experimental data, we form datasets that contain diverse observations with varying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

3
6

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 42 publications
(68 reference statements)
0
6
0
Order By: Relevance
“…Dunne et al suggested that the urination of a patient can be determined by the bladder status. They proposed a method based on machine learning by training the measured voltages [3] and the reconstructed EIT images [8] to determine the bladder status. Schlebusch et al found that urine conductivity significantly affects the measurement accuracy of bladder volume by EIT [9].…”
Section: Introductionmentioning
confidence: 99%
“…Dunne et al suggested that the urination of a patient can be determined by the bladder status. They proposed a method based on machine learning by training the measured voltages [3] and the reconstructed EIT images [8] to determine the bladder status. Schlebusch et al found that urine conductivity significantly affects the measurement accuracy of bladder volume by EIT [9].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, in terms of medical diagnosis and decision-making, deep learning can be used to provide doctors with intelligent auxiliary diagnosis information for quick decision-making. Candiani et al used neural networks to achieve effective classification of brain stroke from EIT results ( Candiani and Santacesaria, 2022 ), whereas Dunne et al used image-based machine learning that provides intelligent monitoring for urinary incontinence patients ( Dunne et al, 2018 ). Moreover, Lee et al (2020) proposed EIT abdominal fat estimation based on deep learning.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, unsupervised filter methods can use the entire dataset in order to rank the features, without biasing the classification result. An unsupervised feature selection algorithm, the Laplacian Score algorithm [55,56], was used in this work to rank the features on the measurement sets (datasets). Specifically, the Laplacian Score algorithm works on the assumption that if two data points are close, then the data points most likely share a label [55].…”
Section: Laplacian Scoresmentioning
confidence: 99%